2022
DOI: 10.2147/idr.s364526
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of NDM-5 Carbapenemase-Encoding Gene (blaNDM-5) – Positive Multidrug Resistant Commensal Escherichia coli from Diarrheal Patients

Abstract: Purpose The multidrug resistance Enterobacteriaceae cause many serious infections resulting in prolonged hospitalization, increased treatment charges and mortality rate. In this study, we characterized bla NDM-5 -positive multidrug resistance commensal Escherichia coli (CE) isolated from diarrheal patients in Kolkata, India. Methods Three CE strains were isolated from diarrheal stools, which were negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…The ECCL209 isolate was assigned as serotype O83:H42 using SerotypeFinder 2.0, 5 which is an extraintestinal pathogenic E. coli (ExPEC) primarily found in samples from animals, indicating their possible transmission from animal to humans (Abreu-Salinas et al, 2020;Shafiq et al, 2021aShafiq et al, ,b, 2022. MLST analysis revealed that E. coli isolate ECCL209 in this study belonged to sequence type (ST648), which had been previously reported to carry bla CTX−M− , bla CMY−2− , bla NDM− , bla OXA−48− , and mcr-1 encoding genes and caused a significant proportion of infections in humans (Hornsey et al, 2011;Poirel et al, 2018;Chowdhury et al, 2022). This clonal lineage has emerged as a pandemic high-risk clone, being globally reported in humans, animals, and the environment (Hornsey et al, 2011;Fernandes et al, 2018;Furlan et al, 2020;Chowdhury et al, 2022;Landolsi et al, 2022).…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…The ECCL209 isolate was assigned as serotype O83:H42 using SerotypeFinder 2.0, 5 which is an extraintestinal pathogenic E. coli (ExPEC) primarily found in samples from animals, indicating their possible transmission from animal to humans (Abreu-Salinas et al, 2020;Shafiq et al, 2021aShafiq et al, ,b, 2022. MLST analysis revealed that E. coli isolate ECCL209 in this study belonged to sequence type (ST648), which had been previously reported to carry bla CTX−M− , bla CMY−2− , bla NDM− , bla OXA−48− , and mcr-1 encoding genes and caused a significant proportion of infections in humans (Hornsey et al, 2011;Poirel et al, 2018;Chowdhury et al, 2022). This clonal lineage has emerged as a pandemic high-risk clone, being globally reported in humans, animals, and the environment (Hornsey et al, 2011;Fernandes et al, 2018;Furlan et al, 2020;Chowdhury et al, 2022;Landolsi et al, 2022).…”
Section: Resultsmentioning
confidence: 58%
“…MLST analysis revealed that E. coli isolate ECCL209 in this study belonged to sequence type (ST648), which had been previously reported to carry bla CTX−M− , bla CMY−2− , bla NDM− , bla OXA−48− , and mcr-1 encoding genes and caused a significant proportion of infections in humans (Hornsey et al, 2011;Poirel et al, 2018;Chowdhury et al, 2022). This clonal lineage has emerged as a pandemic high-risk clone, being globally reported in humans, animals, and the environment (Hornsey et al, 2011;Fernandes et al, 2018;Furlan et al, 2020;Chowdhury et al, 2022;Landolsi et al, 2022). To the best of our knowledge, this is the first report of ST648, with bla NDM and tet(X4).…”
Section: Resultsmentioning
confidence: 58%
“…Conjugation experiments were carried out to determine the transferability of plasmid-mediated bla NDM genes using sodium azide-resistant E. coli J53 as the recipient strain, as previously described ( 28 ). Briefly, isolates were grown on chromogenic media plates with 1 µg/mL meropenem (AstraZeneca, London, UK) and E. coli J53 on chromogenic media with 200 µg/mL sodium azide.…”
Section: Methodsmentioning
confidence: 99%
“…These evidence collectively suggest that the bla NDM-5 -carrying cassette is frequently transferred as an integral complex with class 1 integron rather than as a standalone gene cassette, as also implicated in previous studies with E. coli. 47,48 Nevertheless, future research is necessary to validate the role of class 1 integron and ISCR1 element in the dissemination of bla NDM-5 gene. Using cgSNP-based phylogenetic analysis, we found that A132 shares a close genomic relationship with numerous Chinese S. London ST155 strains retrieved from EnteroBase.…”
Section: Discussionmentioning
confidence: 99%